TELPACK an advanced teletraffic analysis package. - Akar, N. (IEEE Communications magazine)
The performance evaluation of computer and communication networks gives rise to teletraffic problems of potentially large dimensionality. We summarize a unifying system theoretic approach to efficient solution of a diversity of such problems, and introduce TELPACK, a publicly available software that implements this approach